Unleashing Change : A Study of Organizational Renewal in Government - Kelman, Steven (Book collections on Project MUSE., 2005)
"Drawing on the experience of procurement reform in the Reinventing Government initiative of the 1990s, as well as organization theory and psychology, this book presents a comprehensive approach to improving performance in big public sector organizations that addresses both theory and practice"--Provided by publisher